Linkage of bacterial protein synthesis and presentation of MHC class i-restricted Listeria monocytogenes-derived antigenic peptides - Grauling-Halama, Silke; Schenk, Simone; Bubert, Andreas (PLOS ONE, 2012)
The processing and MHC class I-restricted presentation of antigenic peptides derived from the p60 protein of the facultative intracellular bacterium Listeria monocytogenes is tightly linked to bacterial protein synthesis. We used non-linear regression analysis to fit a mathematical model of bacterial antigen processing to a published experimental data set showing the accumulation and decay of p60-derived antigenic peptides in L. monocytogenes-infected cells. Two alternative models equally describe the experimental data. The simulation accounting for a stable and a hypothetical rapidly degraded form of antigen predicts that the antigenic peptides p60 217-225 and p60 449-457 are derived from a putative instable form of p60 with an average intracellular half-life of approximately 3 minutes accounting for approximately 31% of all p60 molecules synthesized. The alternative model predicts that both antigenic peptides are processed from p60 degraded intracellularly with a half-life of 109 min and that antigen processing only occurs as long as bacterial protein synthesis is not inhibited. In order to decide between both models the intracellular accumulation of p60 in infected cells was studied experimentally and compared with model predictions. Inhibition of p60 degradation by the proteasome inhibitor epoxomicin revealed that during the first 3 h post infection approximately 30% of synthesized p60 molecules were degraded. This value is significantly lower than the approximately 50% degradation of p60 that would be expected in the presence of the predicted putative short-lived state of p60 and also fits precisely with the predictions of the alternative model, indicating that the tight connection of bacterial protein biosynthesis and antigen processing and presentation of L. monocyctogenes-derived antigenic peptides is not caused by the presence of a highly instable antigenic substrate.